2020
DOI: 10.1080/14735903.2020.1737356
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Inclusive SAI: contextualizing indicators to better evaluate gender and intergenerational inequity in SAI processes and outcomes – cases from Southern and Western Africa

Abstract: Despite increasing sustainable agricultural intensification (SAI) investments, indicators for detecting gender and intergenerational inequities in SAI costs and benefits sharing often remain overgeneralized, theoretical, or locally irrelevant. We examine the relative value of, and how to, customize standard SAI indicators to detect such inequities in specific socio-cultural contexts to enhance data collection for evidence-based decision making in fostering gender/youth inclusive SAI. Using focus-group discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The testing of these tools demonstrates the feasibility of their use by a wide range of actors, including small NGOs, large businesses, government officers and community-based organizations. Excellent implementation of the tool in the field is only one component of the process that starts with decision makers choosing the most appropriate tool and contextualizing indicators for local conditions (Zulu et al, 2020) to use with the tools. That process culminates with using the data from the tools to inform specific projects and to improve interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The testing of these tools demonstrates the feasibility of their use by a wide range of actors, including small NGOs, large businesses, government officers and community-based organizations. Excellent implementation of the tool in the field is only one component of the process that starts with decision makers choosing the most appropriate tool and contextualizing indicators for local conditions (Zulu et al, 2020) to use with the tools. That process culminates with using the data from the tools to inform specific projects and to improve interventions.…”
Section: Resultsmentioning
confidence: 99%
“…However, asking respondents to recall an entire farming season raises concerns about the accuracy of recall. Stakeholders in Malawi cautioned that questions should be asked as soon after harvest as possible (Zulu et al, 2020). Our experience is that reasonable estimates are possible by walking with farmers to particular fields and asking them to recall how many days (or portions of days) they spent doing major tasks in that place over the past growing season (noting how many people, by gender and age).…”
Section: Tools To Analyse Time Allocationmentioning
confidence: 99%
“…from SAI, and the perceptions of women, youth and elderly regarding the restrictions and enablers of their participation in the transition towards agricultural intensification (Fischer et al, 2020;Lindjö et al, 2020;Zulu et al, 2020). Lindjö et al (2020) observed that young and productive farmers were often lacking access to land, whereas elderly farmers withholding this land were increasingly unable to use this resource productively.…”
Section: Enabling Smallholders To Benefit From Saimentioning
confidence: 99%
“…Supporting decision making on what works and does not work to enable women and youth participation depends on appropriate metrics and indicators that reflect these stakeholders' situations (Grabowski et al, 2020;Zulu et al, 2020). To mitigate potential biases, decision makers must be able to assess if and how access to agricultural resources is differentiated by gender or age, particularly in the context of agricultural changes such as intensification.…”
Section: Enabling Smallholders To Benefit From Saimentioning
confidence: 99%
See 1 more Smart Citation